Challenges and solutions to rural water service sustainability in East African countries: A 'systems scaffolding' perspective. Issue 136 (October 2022) - Walters, Jeffrey; Valcourt, Nicholas; Linden, Karl; Javernick-Will, Amy; Lockwood, Harold
Abstract: This study maps and quantitatively analyzes the interaction of factors that drive (un)sustainable rural water service delivery in five regions across Ethiopia, Uganda, and Kenya by combining the knowledge and experience of 210 service delivery stakeholders, ranging from government officials, service providers and the private sector. We used semi-structured interview data combined with purposive text analysis and a suite of systems analysis tools to map and then structurally analyze leverage points within system maps that characterize challenges and solutions to sustainable rural water service delivery. The analysis of both challenge and solution system maps highlighted the need for more diversified planning and management frameworks centering on coordination, financing, and capacity building that can 'scaffold' effective operation and maintenance activities. The study also expands on a novel process for building and analyzing quantitative systems maps from qualitative interview data. Highlights: Water service sustainability in Africa is a complex and interconnected challenge. Factors driving challenges and solutions to sustainability were modeled as a system. Purposive text analysis was used to build systems models from stakeholder interviews. Diversely supported operation and maintenance programs are key for sustainability. Systemic challenges to water service sustainability require systemic solutions.